Some Fractional Integral Inequalities Involving Mittag-Kernels - Xiujun Zhang; Ghulam Farid; Jiraporn Reunsumrit; Ayyaz Ahmad; Thanin Sitthiwirattham (Journal of Mathematics)
This paper aims to present fractional versions of Minkowski-type integral inequalities via integral operators involving Mittag-Leffler functions in their kernels. Inequalities for various kinds of well-known integral operators can be deduced by selecting specific values of involved parameters. Some particular cases of main results provide connection with the inequalities which have been published in recent years.